2018
DOI: 10.1038/s41598-018-35177-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-mercaptalbumin, Oxidized Form of Serum Albumin, Significantly Associated with Renal Function and Anemia in Chronic Kidney Disease Patients

Abstract: Oxidative stress plays a major role in development of cardiovascular disease in patients with chronic kidney disease (CKD). Human mercaptalbumin (HMA), a reduced form of serum albumin, and non-mercaptalbumin (HNA), an oxidized form of serum albumin, are known as indicators for evaluating oxidative stress in systemic circulation, including end-stage renal disease cases. We investigated factors associated with fraction of HNA [f(HNA)] in 112 pre-dialysis CKD patients (63.6 ± 14.0 years old; 59 males, 53 females)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…The results from our study showed that the percentage of oxidized albumin was significantly higher in the disease model than in the control group and that this change was reversed by the anti-oxidant drug Tempol. These results were consistent with human renal function data 7,29 . To further confirm our results, we have compared serum oxidized albumin with urinary 8-isoprostane levels, which is a commonly used marker to indicate the oxidative stress.…”
Section: Discussionsupporting
confidence: 92%
“…The results from our study showed that the percentage of oxidized albumin was significantly higher in the disease model than in the control group and that this change was reversed by the anti-oxidant drug Tempol. These results were consistent with human renal function data 7,29 . To further confirm our results, we have compared serum oxidized albumin with urinary 8-isoprostane levels, which is a commonly used marker to indicate the oxidative stress.…”
Section: Discussionsupporting
confidence: 92%
“…An exception is a study by Nakatani et al, in which the concentration of PTH correlated with the concentration of the oxidized form of albumin in which the thiol group Cys-34 formed a disulfide bond. However, no similar correlation was found for FGF-23 concentration [226].…”
Section: Parathormon (Pth)mentioning
confidence: 76%
“…Increases in HNA levels have been reported in these patients [11,15,19,32,42]. Most of these studies attended to the sum of oxidized ALB isoforms (i.e., HNA-1 + HNA-2), as determined by HPLC or colorimetric methods [15,19,32,[65][66][67][68][69][70][71]. Still, some studies employed LC-MS/MS and indicated that an increase in cysteinylated ALB level was prominent in CKD patients [11,42].…”
Section: Renal Failuresmentioning
confidence: 99%
“…Still, some studies employed LC-MS/MS and indicated that an increase in cysteinylated ALB level was prominent in CKD patients [11,42]. The oxidized ALB levels paralleled the loss of renal function [32,[67][68][69][70], and "oxidative" uremic toxin has been considered responsible for the ALB oxidation [34,72]. Hemodialysis treatment reversed the serum ALB redox state to a more reduced state [42,65]; reducing agents in dialysis membranes might be involved in the reversal, remaining an open question.…”
Section: Renal Failuresmentioning
confidence: 99%